أثر الإنفاق الحكومي على النمو الاقتصادي في الجزائر - دراسة قياسية خلال الفترة 1986-2017 - مكي عمارية (My University, 2018)
This research aims to study and analyze the impact of public spending on economic growth in Algeria during the period 1986-2017, to address this study and measure the impact of function expenditure and expenditure on equipment resulting real GDP, and in order to test the assumptions adopted through an inductive approach based on ordinary time series and ordinary least squares and models of cointegration and errors correction. The study revealed a number of results: function expenditure that boost economic growth, had a positive impact on real GDP, as opposed to expenditure on equipment, which had a negative impact on economic growth, which was then used as a model of common integration proved that there is a long-term relationship between economic variables in Algeria, and are therefore not far from each other as long as they behave similarly, but for the Model error correction results have concluded that there is a positive and significant effect for the expenditure on equipment effect is corrected each year, as well as the negative impact of function expenditure.
Keywords: economic growth, function expenditure, expenditure on equipment, cointegration, error correction model